Diburu Lensa, Dilindungi Hukum: Urgensi Perlindungan Hukum atas Potret Tak Berizin di Era Aplikasi FOTOYU (LEGAL DIALOGICA, 2025)
This study aims to examine and understand the legal implications and forms of legal protection for portrait objects taken without permission and uploaded to the Fotoyu application. This study uses an empirical legal method with qualitative analysis techniques and will be presented descriptively. The results of the study indicate that taking portraits without permission can lead to criminal and civil charges. The permissive attitude of society is one of the main causal factors. legal protection is needed through a preventive approach, to prevent and limit the use of portraits without permission. The repressive approach is in the form of administrative sanctions, civil lawsuits, and criminal sanctions against perpetrators of violations. This study also highlights the importance of the visual revolution by encouraging the creation of a safer and more ethical photography ecosystem. Reporting violations can be done through the Fotoyu Application, the Ministry of Communication and Digital (KOMINDIGI) and the police. Research recommendations, the need to adopt the concept of fair use in Indonesia, as in the United States, where commercial use is considered reasonable if it is transformative and does not harm the copyright or subject of the portrait. Providing virtual messages on the camera device and special signs on the camera body as a reminder not to take pictures without permission.Abstrak:Penelitian ini bertujuan untuk mengkaji dan memahami implikasi hukum dan bentuk perlindungan hukum terhadap objek potret yang di ambil tanpa izin dan diunggah kedalam aplikasi fotoyu. Penelitian ini menggunakan metode hukum empiris dengan teknik analisis kualitatif dan akan dipaparkan secara deskriptif. Hasil penelitian menunjukkan bahwa pengambilan potret tanpa izin dapat berujung pada tuntutan pidana dan perdata. Sikap permisif masyarakat menjadi salah satu faktor penyebab utama. perlindungan hukum diperlukan melalui pendekatan preventif, untuk pencegahan dan membatasi penggunaan potret tanpa izin. Pendekata reprensif berupa sanksi administratif, gugatan perdata, dan sanksi pidana terhadap pelaku pelanggaran. Penelitian ini juga menyoroti pentingnya revolusi visual dengan mendorong terciptanya ekosistem fotografi yang lebih aman dan etis. Pelaporan pelanggaran dapat dilakukan melalui Apliksi Fotoyu, kementrian komunikasi dan digital (KOMINDIGI) dan kepolisian. Rekomendasi penelitian, perlunya adopsi konsep fair use di Indonesia, seperti di Amerika Serikat, dimana penggunaan komersial dianggap wajar apabila bersifat transformstif dan tidak merugikan hak cipta atau subjek potret. Pemberian pesan virtual pada perangkat kamera dan tanda khusus pada body kamera sebagai pengingat untuk tidak memotret tanpa izin.